Late Triassic island dwarfs? Terrestrial tetrapods of the Ruthin fissure (South Wales, UK) including a new genus of procolophonid. Issue 5 (October 2020) - Skinner, Matthew; Whiteside, David I.; Benton, Michael J.
ABSTRACT: Ancient cave deposits across South Wales and southwest England have yielded Late Triassic to Early Jurassic tetrapod faunas that occupied a sub-tropical island archipelago. Here we present a hitherto little studied fissure at Ruthin Quarry in South Wales. A tooth of the primitive neoselachian shark Rhomphaiodon minor indicates the age of the fissure as early Rhaetian, some 205 Ma, possibly equivalent to the first bone-bed horizons in the Westbury Formation. We identify 11 taxa, including chondrichthyans, procolophonids including a new genus and species named here Smilodonterpeton ruthinensis, rhynchocephalians, the trilophosaurid Tricuspisaurus thomasi and archosaurs, including a small crocodylomorph like Terrestrisuchus . Ruthin is dominated by procolophonids and secondarily by archosaurs. Rhynchocephalians are rare at Ruthin, unlike at penecontemporaneous fissure localities. Many of these faunas are reminiscent of those found in Carnian-Norian deposits from North America, some of them 25 Myr older, suggesting the Ruthin faunas are relictual. In exploring the palaeogeography of Ruthin and other British Late Triassic fissure deposits, we find that factors in addition to island size may affect the recorded species richness of these islands. Further, most of the taxa appear to be 'primitive' (i.e. possess closest relatives that are much older stratigraphically), and their body sizes are small, so this could be the oldest record of insular dwarfism.